Prioritizing the protection of climate refugia: designing a climate-ready protected area network. Issue 14 (6th December 2019) - Graham, Victoria; Baumgartner, John B.; Beaumont, Linda J.; Esperón-Rodríguez, Manuel; Grech, Alana
Abstract : Protected areas are the primary strategy for maintaining natural landscapes and separating biodiversity features from preventable anthropogenic threats. The Convention on Biological Diversity calls for the coverage of at least 17% of land by protected areas, and the strategic prioritization of important biodiversity areas. Using the spatially explicit reserve design software, Marxan, this study combines climate refugia modelled under future climates in the year 2070 and bioregions to identify priority sites for protected area expansion under climate change in the state of New South Wales (NSW), Australia. Priority sites for new protected areas that meet bioregion and climate refugia targets were identified in central-western, northeast and patches of southeast NSW. Seven existing parks, including Kosciuszko National Park, overlapped with regions identified repeatedly as climate refugia under 12 future climate scenarios. The recommendations from this study support policy-makers in prioritizing the protection of biodiversity under a changing and uncertain climate.